2016
DOI: 10.1111/bjd.14604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of screening questionnaires to identify psoriatic arthritis in a primary-care population: a cross-sectional study

Abstract: Summary Background Many questionnaires are available for assessment of psoriatic arthritis (PsA), but there is little evidence comparing them. Objectives To test the proposed CONTEST questionnaire, which was developed to identify patients with psoriasis who have undiagnosed PsA, and compare it with the validated Psoriasis Epidemiology Screening Tool (PEST) questionnaire in a primary‐care setting. Methods A random sample of adult patients with psoriasis and no diagnosis of arthritis was identified from five gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 15 publications
(21 reference statements)
3
30
0
Order By: Relevance
“…Overall, our results are very much in line with the recently published data by Coates et al ., thereby providing additional validity of these observations. Using the PEST as the sole determinant to refer patients may place a greater burden on the capacity of the rheumatologist, but there are ways of overcoming this challenge.…”
Section: Evaluation Of the Psoriasis Epidemiology Screening Tool (Pesmentioning
confidence: 80%
See 2 more Smart Citations
“…Overall, our results are very much in line with the recently published data by Coates et al ., thereby providing additional validity of these observations. Using the PEST as the sole determinant to refer patients may place a greater burden on the capacity of the rheumatologist, but there are ways of overcoming this challenge.…”
Section: Evaluation Of the Psoriasis Epidemiology Screening Tool (Pesmentioning
confidence: 80%
“…The Psoriasis Epidemiology Screening Tool (PEST) is a short screening questionnaire that could guide dermatologist decision making, and Coates et al . have provided evidence that the PEST may be used in both primary and secondary care settings . One key finding is that they have questioned the original PEST cut‐off score that would warrant rheumatologist referral, with their data now suggesting that a lower cut‐off point may be more appropriate .…”
Section: Evaluation Of the Psoriasis Epidemiology Screening Tool (Pesmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides evidence that the meta-analysed questionnaire screening tools are not only similar to each other in terms of structure, time to complete (between 510 min) [8,10] and validation setting, but also in terms of accuracy. Other questionnaire tools such as the CEPPA, CONTEST and GEPARD have tried to put together different parts of other questionnaires to create a new and improved version [20,27,35]. However, separate studies do not appear to present compelling evidence of superior screening accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…There are significant delays in diagnosis for the majority of patients (typically, in screening studies, up to 50% of established cases have not previously been identified). 7 Delay in diagnoses of 6 and 12 months have been shown to impact on long-term joint damage and functional disability.…”
Section: Psoriatic Arthritis: State Of the Art Reviewmentioning
confidence: 99%